The age of melt : what glaciers, ice mummies, and ancient artifacts teach us about climate, culture, and a future without ice - Baril, Lisa (Timber Press, 2024)
"An exploration of ice-patch archaeology and the ... story of how glaciers play a crucial role in human culture."--Flap page 1 of dust jacket.